SPECIFICATIONS OF ECO-MATERIALS AND THEIR INFLUENCE IN THE DESIGN OF MODERN FURNITURE - Namicev, Petar; Tasevska, Viktorija (Journal of process management and new technologies, 2019)
The materials are an important segment of everyday life and their choice in the production of products is of a great importance. The choice of materials is influenced by certain technical requirements that are necessary to be met, and those requirements are density, strength, temperature stability, price, and material resistance. According to the origin, the materials are divided into natural/eco-materials and artificial/conventional. Eco materials are natural resources that are obtained directly from nature and can have a variety of benefits in the design of the home. The human and nature’s symbiosis is an important foundation in the modern design industry. Adding the same to the home brings the warmth felt in nature. In the manufacture of modern furniture the following eco-materials are used: wood, stone, leather, metals, bamboo, cork and natural fibres. All these materials provide a pleasant ambience that is in harmony with nature without harming people’s health. The wood used in the manufacture of furniture introduces warmth, naturalness, and attractiveness. The natural stone most often has a decorative role in the making of furniture. Natural leather is used for upholstery of furniture to add comfort and softness. Metal is used in furniture in order to give a special look. The bamboo has a significant role in furniture manufacture and is characterized by high toughness, easy processing, and durability. The cork, besides being used for insulation, has also been used in the manufacture of furniture, as well as decorative material. Natural fibres are used for upholstery of furniture and as floor coverings.